Synthesis and characterization of activated carbon from biowaste-walnut shell and application to removal of uranium from waste - Yaman, M.; Demirel, M. H. (Univ Tehran, 2020)
The aim of this study is to synthesize and characterize an economical and environmentally-friendly adsorbent with high adsorption capacity. For this purpose, the walnut shells (Juglans regia L.) were chemically modified using sulfuric and citric acids, separately. After pyrolysis and synthesis of activated carbon (AC), the optimization of conditions at the preconcentration/removal step was performed using parameters such as pH and contact time for uranium in the model solutions. The measurements were carried out by inductively coupled plasma-mass spectrometry (ICP-MS). From the shapes of the BET isotherms, it may be stated that activated carbon exhibit type I. It was found that the surface area and total pore volume of the activated carbon were 696.6 m2/g and 0.35 mL/g, respectively. The adsorption capacity was found to be 220 mg/g. It was found that the optimum pH is 6.0 for preconcentration/removal using AC obtained by sulfuric acid as chemically-modifier. The optimized method was applied to determination of U at ng/mL levels in the model solutions.
Keywords: Preconcentration; adsorbent; toxic element; biomass